2020
DOI: 10.1101/2020.07.10.197921
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluating High Spatial Resolution Diffusion Kurtosis Imaging at 3T: Reproducibility and Quality of Fit

Abstract: Background Diffusion kurtosis imaging (DKI) quantifies the microstructure non-Gaussian diffusion properties. However, it has increased fitting parameters and requires higher b-values. Evaluation of DKI reproducibility is important for clinical purposes. Purpose To assess reproducibility in whole-brain high resolution DKI at varying b-values. Study Type Prospective. Subjects and Phantoms Forty-four individuals from the test-retest Human Connectome Project (HCP) database and twelve 3D-printed tissue mimicking ph… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 35 publications
1
8
1
Order By: Relevance
“…Each optimal b ‐value combination included unequally spaced b ‐values, a result consistent with similar DKI experiments 27,28 . A reproducibility study also concluded that DKI fits to b ‐values of 1000 and 3000 s mm −2 showed lower coefficients of variation than to 1000 and 2000 s mm −2 43 . These previous studies used maximum b ‐values within the range commonly used for DKI, whereas we showed that a larger b ‐value range is well‐fitted by the MLF.…”
Section: Discussionsupporting
confidence: 74%
“…Each optimal b ‐value combination included unequally spaced b ‐values, a result consistent with similar DKI experiments 27,28 . A reproducibility study also concluded that DKI fits to b ‐values of 1000 and 3000 s mm −2 showed lower coefficients of variation than to 1000 and 2000 s mm −2 43 . These previous studies used maximum b ‐values within the range commonly used for DKI, whereas we showed that a larger b ‐value range is well‐fitted by the MLF.…”
Section: Discussionsupporting
confidence: 74%
“…The scan time is mainly determined by the number of b‐values and it should be kept in mind that b‐values above 3000 s/mm 2 result in poorer fit quality 34 . Kasa et al 10 demonstrated that comparable reproducibility can be obtained by using either a three or a two multishell protocol with lower b‐values; the latter is the study protocol we opted for in this study. Technologies such as multiband might enable doubling the number of directions acquired in the same time, which will probably further reduce the CV.…”
Section: Discussionmentioning
confidence: 99%
“…However, only a few studies have investigated the test–retest reliability of DKI in the brain in healthy individuals 10–12 : of these, one study was conducted in three patients with traumatic brain injury and four healthy controls (HCs), 13 and one study in small vessel disease, 14 reporting good to excellent test–retest reproducibility. Of all these studies, only two included gray matter (GM) regions in their test–retest assessment 10,11 …”
Section: Introductionmentioning
confidence: 99%
“…As dMRI has reached the forefront of tissue microstructure imaging [40], there is a need to establish the reproducibility of these emerging methods. While the reproducibility of DTI and DKI has been investigated extensively [41][42][43][44], to the best of our knowledge, no test-retest assessment of OGSE and µA dMRI has been done at an ultra-high field strength. The aim of this work was to assess test-retest reproducibility of in vivo OGSE and µA dMRI in mice at 9.4 Tesla and provide estimates of required sample sizes, which is essential in planning future preclinical neuroimaging studies involving models of disease/injury.…”
Section: Introductionmentioning
confidence: 99%